Foundations of Statistical Natural Language Processing: A Case Study of Text Input System - Gao, Jianfeng; Suzuki, Hisami (2007)
Tutorial slides at the MSR Weihai Summer School, August 2007.
Tutorial slides at the MSR Weihai Summer School, August 2007